Changes in Compositional Properties during Fruit Development and On-Tree Ripening of Two Common Apricot (Prunus armeniaca L.) Cultivars - Karabulut, Ihsan; Ozdemir, Ibrahim S.; Koc, Tugca B.; Sislioglu, Kubra; Gokbulut, Incilay; Saritepe, Yuksel (Wiley-V C H Verlag Gmbh, 2021)
The objective of the present study was to investigate the variations in some major primary (sugars and organic acids) and secondary (phenolics, beta-carotene) metabolite contents during fruit development and ripening in two important apricot cultivars (Hacihaliloglu and Kabaasi). The changes in the compositional properties of two apricot cultivars were monitored during fruit development with one-week intervals from 56 to 119 days after blossom. During fruit development, the contents of organic acids and phenolics decreased whereas that of sucrose and sorbitol increased. p-Coumaric acid was the only phenolic compound which increased in concentration during fruit development regardless of the cultivar. The content of the other phenolic compounds decreased in a cultivar-dependent manner. The beta-carotene content of the cultivars showed distinct patterns of change such that 3 fold increase in beta-carotene content of Kabaasi cultivar was observed whereas the beta-carotene content of the Hacihaliloglu cultivar did not show any significant change during fruit development.
Keywords: apricot; carotenoid; metabolism; phytochemistry; ripening; phenolic